2013
DOI: 10.1177/1358863x13503192
|View full text |Cite
|
Sign up to set email alerts
|

A slightly high-normal glucose level is associated with increased arterial stiffness in Japanese community-dwelling persons with pre-diabetes

Abstract: Impaired fasting glucose (IFG) in diabetes is a risk factor for arterial stiffness and cardiovascular disease (CVD), but the impact of a slightly high-normal glucose level remains controversial. We investigated whether slightly high-normal fasting plasma glucose (FPG) was independently associated with arterial stiffness in non-diabetic community-dwelling persons. We recruited 114 men aged 69 ± 9 years (range 40-89) and 208 women aged 68 ± 7 years (range 36-84) during their annual health examination in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…46) Hence, there are some common mechanisms underlying Hcy and FBG leading to arterial stiffness, such as endothelial dysfunction and collagen synthesis. 17) Similarly, our study demonstrated that the coexistence of high FBG and Hcy levels can increase baPWV more than FBG or Hcy alone.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…46) Hence, there are some common mechanisms underlying Hcy and FBG leading to arterial stiffness, such as endothelial dysfunction and collagen synthesis. 17) Similarly, our study demonstrated that the coexistence of high FBG and Hcy levels can increase baPWV more than FBG or Hcy alone.…”
Section: Discussionsupporting
confidence: 70%
“…16) The progressive relationship between glucose level and arterial stiffness extends below the diabetic threshold. 17) Previous studies suggest that increased fasting plasma glucose (FPG), which includes impaired glucose tolerance (IGT), impaired fasting glucose (IFG), and diabetes mellitus (DM), is a risk factor for arterial stiffness. [18][19][20] Homocysteine (Hcy), a sulphur-containing amino acid produced by the catabolism of dietary methionine, is a known risk factor for the cardiovascular system.…”
mentioning
confidence: 99%
“…This may be related to a lower prevalence of diabetes among women (13.3%). In addition, some studies have reported that increased arterial stiffness was not only associated with subjects in diabetes mellitus but also in healthy subjects with impaired fasting glucose 30 or high-normal glucose level 31 . This may partially explain why it’s FBG not diabetes mellitus was independently associated with arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The PWV is an established index of arterial stiffness 22 , and the ba-PWV has characteristics similar to the central aortic PWV 23 . The underlying mechanisms responsible for arterial stiffness are unknown; however, slightly high-normal glucose levels were reported to be associated with arterial stiffness measured using ba-PWV 24 . Indeed, IFG is known to be a risk factor for arterial stiffness and CVD, and the ba-PWV value in the IFG group was significantly higher than the value in the NFG group 24 .…”
Section: Discussionmentioning
confidence: 99%